Role of bronchoalveolar lavage fluid and serum interleukin-27 in the diagnosis of smear-negative pulmonary tuberculosis. Issue 20 (21st May 2021) - Zhu, Feng; Ou, Qinfang; Zheng, Jian; Zhou, Min; Chen, Huaxin; Jiang, Xiufeng
Abstract: Background: To evaluate the value of interleukin (IL)-27 measured in serum and bronchoalveolar lavage fluid (BALF) for the diagnosis of smear-negative pulmonary tuberculosis (TB). Methods: This was a prospective study of patients planned to undergo bronchoscopy at Wuxi No.5 People's Hospital between January 2017 and September 2018. The patients were grouped as the TB and control groups. BALF and serum IL-27 were measured by ELISA. Receiver operating characteristic (ROC) curves were used to assess the diagnostic value and calculate the optimal cutoff values. Results: There were 40 patients in the control group and 87 in the TB group. In the TB group, 20 had positive sputum smear results and 67 were negative. The area under the ROC curve (AUC) of BALF IL-27 for pulmonary TB was 0.897 (95% CI: 0.830–0.944) ( P  < .001). The AUC of serum IL-27 for pulmonary TB was 0.703 (95% CI: 0.616–0.781) ( P  < .001). In patients with negative sputum smear results, the AUCs of BALF IL-27 and serum IL-27 for pulmonary TB was 0.882 (95% confidence interval [CI]: 0.805–0.936) ( P  < .001) and 0.679 (95% CI: 0.601–0.782) ( P  < .001), respectively. Conclusions: BALF IL-27 can be used for the diagnosis of pulmonary TB, particularly in those with a negative sputum smear result. Serum IL-27 could be an auxiliary method for TB screening.